ANALYSIS OF KNOWLEDGE STUDENTS IN COMPLETING ASSOCIATION OPERATION PROBLEMS - Gamar Assagaf; Nur Apriani Nukuhaly (MATEMATIKA DAN PEMBELAJARAN, 2021)
Abstract Procedural knowledge is knowledge about the steps that must be taken to solve a problem and can represent mathematical ideas and procedures used to solve a mathematical problem. This study aims to analyze students' procedural knowledge in solving problems on set operation material. This research is a qualitative descriptive study conducted at SMP Muhammadiyah Melati. The subjects of this study were two students who were known to have criteria for procedural knowledge. The research instrument consisted of test questions on the set material and interview guidelines. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. The results showed that the SL subjects in solving questions and interviews could solve the problems posed and meet the three indicators of procedural knowledge. Indicators of procedural knowledge used by researchers in this study are implementing appropriate procedures correctly, communicating algorithmic processes into problem situations, and modifying procedures to deal with factors in problem solving. Keywords: Procedural Knowledge, Problem Solving, Set Operation.